Hadits Maudhu’ (Palsu): Studi Sejarah, Ciri, Dan Upaya Ulama Dalam Menjaga Keaslian Sunnah - Fikri Jayyid, Difa’ul; Isa Anshory, Muhammad (Jurnal Ilmu Ekonomi, Pendidikan dan Teknik, 2025)
False hadith (maudhu’) represent a serious challenge to the preservation and practice of Islamic teachings. The emergence of fabricated hadith has been rampant since the death of the Prophet Muhammad (peace be upon him), especially during periods of political and ideological conflict among Muslims, such as during the Caliphate of Ali ibn Abi Talib. These hadith were created by various parties to support the interests of certain groups, whether in political or ideological contexts, or for personal gain. This study aims to examine in depth the history of the emergence of fabricated hadith, identify the criteria for fabricated hadith, and analyze the various efforts of scholars to maintain the authenticity of hadith. Using qualitative methods based on literature review, this study draws on classical literature such as Ibn al-Jawzi's Al-Maudhu’at, al-Kamil fi Du'afa' al-Rijal, and contemporary academic journals as secondary sources. The research results show that fabricated hadith can be identified by characteristics such as unreliable sanad (chain of transmission), contradictions with the Qur'an and authentic Sunnah, contradictions with the consensus of scholars, and irrational or exaggerated content. On the other hand, scholars have responded to this phenomenon by developing the science of hadith, compiling authentic books, implementing the science of jarh wa ta'dil (examination), and providing education and outreach to the public. Even in the digital era, scholars and religious institutions continue to strive to educate the public about identifying fabricated hadith through technology platforms. This research is expected to be an important contribution to strengthening Islamic literacy and serve as a foundation for further research in the field of hadith criticism and contextual religious education.